A fierce and subtle poison - Mabry, Samantha (2016)
Spending the summer with his hotel-developer father in Puerto Rico, seventeen-year-old Lucas turns to a legendary cursed girl filled with poison when his girlfriend mysteriously disappears
Keywords: Paranormal fiction; Poisons -- Fiction; Romance fiction; Puerto Rico -- Fiction